A Guerra do Paraguai conforme Roa Bastos - Wimmer, Norma [UNESP] (2010)
This paper analyzes texts on the Paraguayan War (1864) written by Roa Bastos, Alexandro Maciel, Omar Prego Gadeia, Eric Nepomuceno, published in the book O livro da Guerra Grande (2002), translated from the Spanish Los Conjurados del Quilombo del Gran Chaco (2001).